Epistemological Multilingualism: A Tool for Conviviality - Scott, Charles (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2009)
In a globalized world where the traditional, the modern, and the postmodern increasingly meet, there is a growing need for understanding, particularly of views different from our own. In this paper, I want to explore the concept of epistemological multilingualism and its value to scholarship, advancing the notion that epistemological multilingualism—the ability to respect and understand multiple epistemic standpoints—emerges out of a postmodern, integral perspective which sees the reality of several epistemological frameworks, as well as the ability to understand, learn from, and even to contribute to the development of those frameworks. I examine the dialogical capacities that contribute to epistemological multilingualism, and conclude that epistemological multilingualism can play a vital role in a world of education where differing worldviews manifest within the same classroom and the lives of the learners with whom we work.